NON-OPIOID MULTIMODAL ANALGESIA USING IBUPROFEN AND PARACETAMOL DURING ABDOMINAL SURGERY IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Optimize perioperative anesthesia in children who have undergone abdominal surgery by using multimodal non-opioid analgesia with a combination of ibuprofen and paracetamol.
Keywords: multimodal analgesia; ibuprofen; paracetamol; children; postoperative; pain syndrome; opioids